Catchment‐scale applications of hydraulic habitat models: Climate change effects on fish. Issue 3 (9th December 2022) - Morel, Maxime; Pella, Hervé; Branger, Flora; Sauquet, Eric; Grenouillet, Gaël; Côte, Jessica; Braud, Isabelle; Lamouroux, Nicolas
Abstract: Approaches available for estimating the ecological impacts of climate change on aquatic communities in river networks range from detailed mechanistic models applicable locally to correlative approaches applicable globally. Among them, hydraulic habitat models (HABMs) link hydraulic models of streams with biological models that reflect how organisms select microhabitat hydraulics. Coarser but more general species distribution models (SDMs) predict changes in geographic distributions; they generally involve coarse predictors such as air temperature or distance to source but neglect proximate habitat descriptors such as microhabitat hydraulics. We propose an original application of HABM for predicting the ecological impacts of climate change at large scales, a comparison of their predictions with those of SDM and a linkage of the two modelling approaches. We showcase our approach in a large catchment (Rhône River) where an available distributed hydrological model estimates present and future unregulated daily flows over the whole river network. Despite large local uncertainties, simulations showed that climate change may strongly reduce low flow percentiles (e.g., a median reduction of 38.6% for a pessimistic climate scenario), inducing important alteration of fish hydraulic habitat suitability (e.g., a median loss of 3.9%–18.7% for three modelled fish species with contrasting habitat use: brown trout, barbel and sculpin). The HABM and SDM individually predicted consistent or opposite fish responses to climate change, depending on the species and their habitat requirements. Our results illustrate that accounting for ecological responses to proximate habitat variables such as hydraulics can strongly modify projections related to climate change.